Patternless sewing MODstyle : 24 garments for women and girls : just measure, cut & sew for the perfect fit! - Young, Patty Prann, 1971- (Stash Books, an imprint of C&T Publishing, 2016)
Presents instructions for patternless garments for women and girls, offering a flattering fit for all body types and ways to personalize each look.